+0  
 
0
268
3
avatar+4 
would someone please factor this for me? its driving me insane!
here it is:

(x^8) -1

thanx!!
PB&J sammiches  May 10, 2012
 #1
avatar
0
(X^8)-1 =((x^4)^2)-1^2=[((x^2)^2) -1^2][(x^4)+1]
=[(x^2)-1^2][(x^2)+1][(x^4)+1]
=[x-1][x+1][(x^2)+1][(x^4)+1]
Guest May 10, 2012
 #2
avatar
0
(x^8) -1

since 8 can be divide by two
8 / 2 = 4

definition of sum and difference
a^2 - b^2 = (a - b)(a + b)

we get,
((x^4) - 1)((x^4) + 1)


since 4 can be divide by two
4 / 2 = 2

((x^4) + 1)((x^2) + 1)((x^2) - 1)


since 2 can be divide by two
2 / 2 = 1

((x^4) + 1)((x^2) + 1)(x - 1)(x + 1)
Guest May 11, 2012
 #3
avatar
0
(4x+1)(4x-1)
Guest May 13, 2012

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.